Different COVID-19 mRNA-based Vaccine Platforms as The Booster Dose and Their Impact on Omicron: A Literature-Based Overview - Mahdi, Bagus Aulia; Soegiarto, Gatot; Wulandari, Laksmi; purnomosari, dewajani (Institute of Topical Disease Universitas Airlangga, 2023)
Globally, the vaccine has been determined as one of the principal policies to tackle the COVID-19 pandemic. However, some vaccinated individuals with two complete doses of inactivated experienced SARS-CoV2 infection, including the healthcare workers (HCWs). This threat led to the emergent need for a vaccine booster with different types of platforms aiming to enhance immunity from the Omicron variant. We conducted a literature study on the concept of heterologous compared to homologous vaccines in COVID-19 vaccination. We obtained 22 studies about COVID-19 booster vaccines. Referring to seven of them, we compared and distinguished between heterologous and homologous vaccines. We then reported the literature review according to PRISMA guideline. The study demonstrated qualitatively that heterologous vaccinations boosted antibody receptor binding domain, neutralizing antibody, and spike-specific Th1 type T cell responses and had an impact on omicron infection when compared to homologous vaccines. In conclusion, heterologous, mRNA based vaccine, predominantly induces cellular and humoral responses better than the homologous vaccine. This increased immune response is expected to provide profound immunity against the Omicron.